Truth That Matters : The Bible's Message for you. - Hayden, Keavin (Pacific Press Publishing Association, 1997)
In this book Keavin Hayden spotlights essential spiritual truths things everyone needs to know, but few take the time to discover for themselves. Truth about the spiritual powers that influence our lives. Truth about the future of our world. Truth that can help you make important decisions.